Inovasi E-modul Berbasis Kearifan Lokal untuk Meningkatkan Minat Belajar Bahasa Arab Siswa Madrasah Aliyah - Shofiyani, Amrini; Mukti, Rangga; Khasairi, Moh. (Study Program of Arabic Language Teaching, 2025)
This study aims to develop an Arabic e-learning module based on local wisdom and test its effectiveness in increasing the learning interest of tenth-grade students. This study is important because learning interest impacts language comprehension and mastery. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The researcher selected a population of tenth-grade students at a senior high school implementing the independent curriculum. The sampling technique used was simple random sampling, conducted randomly without considering strata within the population. The research subjects comprised 30 tenth-grade students in class G at the Senior High School (MAN 4 Jombang) in East Java. The research instruments included expert validation sheets, student response questionnaires, and pretest-posttest questions. Data were analyzed using descriptive and inferential quantitative statistics through the Shapiro-Wilk normality test, Levene's homogeneity test, and paired t-test. The results showed that the developed e-module was valid and feasible based on assessments by content and media experts. Statistical tests showed a significant increase in student scores after using the e-module, with an average pretest score of 44.27 and an average posttest score of 84.93. The paired t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between students' learning outcomes before and after using the e-module. Therefore, the e-module based on local wisdom is effective and highly recommended as a teaching material in improving students' interest and performance in learning Arabic.